1998
DOI: 10.1002/(sici)1097-0142(19980101)82:1<186::aid-cncr24>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Taurine attenuates recombinant interleukin-2-activated, lymphocyte-mediated endothelial cell injury

Abstract: BACKGROUND. Recombinant interleukin-2 (rIL-2) immunotherapy is limited by mi-Nicola M. Finnegan, B.A.Mod. crovascular endothelial cell (EC)-targeted injury. The interaction between rIL-2-H. Paul Redmond, F.R.C.S.I. activated lymphoid cells and EC is a possible mechanism of this systemic toxicity. David J. Bouchier-Hayes, F.R.C.S.I. Taurine, a b-amino acid, is known to have several physiologic actions, including the modulation of calcium homeostasis. The aims of this study were to analyze Department of Surgery,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…18 It has been shown to stimulate T and B lymphocytes in response to mitogens and reported to play a dual role in recombinant interleukin-2 immunotherapy, due to its ability to reduce the vascular injury associated with this therapy while enhancing its antineoplastic activity. 10 The result of the present study showed that the physiological concentration of taurine decreases MMC-induced SCE in infants lymphocytes. We suggest that the high levels of taurine found in the human milk may induce protecting effects of BF against DNA damage and malignancy.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…18 It has been shown to stimulate T and B lymphocytes in response to mitogens and reported to play a dual role in recombinant interleukin-2 immunotherapy, due to its ability to reduce the vascular injury associated with this therapy while enhancing its antineoplastic activity. 10 The result of the present study showed that the physiological concentration of taurine decreases MMC-induced SCE in infants lymphocytes. We suggest that the high levels of taurine found in the human milk may induce protecting effects of BF against DNA damage and malignancy.…”
Section: Discussionsupporting
confidence: 53%
“…Taurine is reported to be the most abundant free amino acid in lymphocytes (44%) 10 . Its concentration in leukocytes is reported to be between 20–50 mM 11 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The protective effects of taurine may be explained by its detoxification of hypochlorous acid, a potent oxidant that can cause extensive tissue damage. However, recent evidence from our laboratories [10][11][12][13][14][15][16] and others [17][18][19] demonstrates that taurine chloramine (Tau-Cl), produced from highly toxic hypochlorous acid and taurine, is thought to be pivotal in regulating inflammation. Our previous data demonstrate that Tau-Cl inhibits proinflammatory mediators such as NO and TNF-α in a variety of both primary macrophages and cultured macrophagelike lines from rodents [10,13].…”
Section: Introductionmentioning
confidence: 99%
“…Such antidote effects of taurine or high capacity for taurine uptake into the cells (or conversely harmful effects of taurine depletion) have i.a . been found against alcohol (2340), against the analgesic and fever-depressing drug acetaminophen (also called paracetamol) (4144), against the aminoglycoside antibacterial drug gentamicin (4547), against the immunosuppressant drug cyclosporine A (48, 49), against the anticancer drugs cisplatin (5054), doxorubicin (also called adriamycin) (5562), bleomycin (6378), methotrexate (79) and taumustine (80), against the cytokine interleukin-2 (IL-2), which is used for immunotherapy of cancer (8184), against the estrogen receptor modulator tamoxifen, which is used in therapy of breast cancer (8587), against the antiarrhythmic drug amiodarone (88), against the beta -adrenergic agonists isoproterenol (55) and isoprenaline (8992), against nicotine (9395), against oxidized low-density lipoprotein (LDL) (96), against oxidized fish oil (97), against high glucose levels (96, 98110), against fructose (111122), against galactose (123), against advanced glycation end-products (AGEs) (100, 124, 125), against homocysteine (126–130), against the anti-inflammatory drugs ibuprofen (131) and indomethacin (132, 133), against the herbicide paraquat (65, 134, 135), against carbon tetrachloride (136149), against menadione (150), against 1,4-naphtoquinone (137, 139), against hydrazine (137, 139), against trinitrobenzene sulfonic acid (151, 152), against acrylonitrile (153), against perchloroethylene (154), against methylene dianiline (155), against arsenic (156164), against cadmium (…”
Section: Evidence Showing That Taurine Functions As a Biological Antimentioning
confidence: 99%